Ana M. López : essays - López, Ana M. (State University of New York Press, 2023)
"Brings together Ana M. López's field-defining essays on Latin American film and media in one indispensable volume"-- Provided by publisher.
Keywords: Motion pictures -- Latin America -- History.; Motion pictures -- Social aspects -- Latin America.; Mass media -- Latin America -- History.; Mass media -- Social aspects -- Latin America.; Latin Americans in motion pictures.; Performing arts.; Video recordings.; Electronic books.; Cinéma -- Amérique latine -- Histoire.; Cinéma -- Aspect social -- Amérique latine.; Médias -- Amérique latine -- Histoire.; Médias -- Aspect social -- Amérique latine.; Latino-Américains au cinéma.; Arts du spectacle.; Vidéos.; Livres numériques.; performing arts (discipline); video recordings (physical artifacts); e-books.; PERFORMING ARTS / Film & Video / History & Criticism.; Latin Americans in motion pictures; Mass media; Mass media -- Social aspects; Motion pictures; Motion pictures -- Social aspects; Latin America; History